Electrical Conductance Device for Stent Sizing - Kassab, Ghassan S. (Frontiers in Physiology, 2019)
The minimum stent area (MSA) has been clinically established as a significant predictor of restenosis, thrombosis, and ischemia using intra-vascular ultrasound (IVUS). Unfortunately, IVUS measurements are far from routine because of significant cost of IVUS, the training required, the subjectivity of image interpretation and the time added to the procedure. The objective of this study is to verify the accuracy of a conductance catheter for stent sizing. Here, we introduce an easier and entirely objective device and method for real time determination of MSA. A 10 kHz, 35µA rms current is passed through the external electrodes of an intravascular catheter while the conductance is measured across a separate set of electrodes. Both phantom and ex vivo validations of metal stent sizing in five porcine carotid arteries were confirmed. The accuracy of the measurements were found to be excellent in phantoms (root mean square, rms, of 3.4% of actual value) and in ex-vivo vessels (rms=3.2% of measured value). An offset of conductance occurs when a conductive metal stent (e.g., bare metal stent) is deployed in the vessel, while the slope remains the same. This offset is absent in the case of drug eluting stent where the metal is coated (i.e., insulated). The present device makes easy, accurate and reproducible measurements of the size of stented blood vessels within 3.2% rms error. This device provides an alternative method to sizing of stent (i.e., MSA) in real-time without subjective interpretation and with less cost than IVUS.